EFFICACY OF THREE MANGROVE PLANTS AGAINST 5-LIPOXYGENASE, ACETYLCHOLINESTERASE ENZYMES AND FIVE PATHOGENIC BACTERIAL STRAINS - Eldeen, Ibrahim; Napiah, Nor Emera .M.; Mohamad, Habsah (LIFE: International Journal of Health and Life-Sciences, 2015)
Mangroves are highly productive ecosystem with various important economic and environmental functions. They are the key elements in marine environment that produce diverse metabolites to adapt with the requirement of their challenging ecosystem. This make them an interesting source for natural bioactive molecules. In this study, we investigated inhibitory effects of extracts from Avicenna lanata, Ceriops tagal and Sonneratia alba against 5-lipoxygenase, acetylcholinesterase enzymes and four pathogenic bacterial strains using in vitro models. Best dual inhibitory effects against the two enzymes was recorded for the methanolic and ethylacetate bark extracts (final concentration used in the assay was 90 μg/ml) of Sonneratia alba and dichlro-root extarct of C.tagal (inhibition percentage ranging between 74-91%). Roots of Ceriops tagal showed the highest activity against lipoxygenase (93%), but was slightly weaker against AchE (83%). Antimicrobial properties of the extracts was determined using the microdilution assay. A. lananta (bark) showed the best antimicrobial efects with the lowest minimum inhibitory concentration (MIC) value of 90 μg/ml against S.aureus, E.coli and K. pneumoniae. Methanolic root and leaf extracts of C.tagal showed the same MIC values against S.aureus. Phytochemical analysis indicated the presence of alkaloids, steroids and tannins in the investigated plant parts. These results support the ethnobotanical uses of these plants. Chemical profiling, isolation and determination of mechanism of actions of the observed bioactivities are currently in progress in our laboratory.